Human Trafficking in Nahum - Cook, Gregory (2015)
Nahum has come under recent censure for the term זונה (3:4). Scholars have argued that calling Nineveh a prostitute does not fit the brutal Neo-Assyrian Empire. This article argues that the book of Nahum charges Nineveh with multi-national human trafficking. Assyrian practices conform to the United Nations definition of human trafficking. The methods Assyria used to recruit, transport, and prostitute peoples match methods of modern slavers. The title זונה therefore is used because the city acted as a spiritual madam. Vast populations were kidnapped for economic purposes and much of the labor, money, and people acquired through conquest were used to serve the Assyrian pantheon.
Keywords: Nahum -- Assyria -- Ishtar -- Feminist Criticism